Relationship of Self-control and Media Exposure with Premarital Sexual Behaviour in Senior High School Students - Adinda Safira Amin, Nada; Eko Wardani, Hartati; Ekawati, Rany (KnE Life Sciences, 2021)
Premarital sexual behaviour is a social phenomenon that is common today. Modernization is one of the reasons for various parties to share pornographic behaviour on the pretext of being a medium for sexual knowledge. Adolescents with good self-control will be able to control negative behavioural impulses from external factors such as premarital sexual behaviour. This study aims to determine the relationship of self-control and media exposure with premarital sexual behaviour in 11th-grade students of Senior High School “X” in Malang City. The study utilized a correlational quantitative method with a cross-sectional design. A total of 76 students, selected using a simple random sampling technique, were included in the study. Data were collected through a questionnaire and analysed using a linear regression analysis with a significance level of (α = 5%) = 0.05. The study found that self-control and information media were both partially and simultaneously related to the premarital sexual behaviour in adolescents. Based on the analysis, the beta value of the selfcontrol was β = 0.303, and that of the information media was β = 0.227. This indicated that the self-control variable had the most dominant relationship with premarital sexual behaviour. Further, the R-Square value was 0.416, which meant premarital sexual behaviour in 41.6% of the 11th-grade adolescents of Senior High School “X” in Malang City was related to two independent variables, self-control and information media. Keywords: adolescent, self-control, media exposure, premarital sexual behaviour